Biochemical and Structural Characterization of Enolase from Chloroflexus aurantiacus: Evidence for a Thermophilic Origin - Zadvornyy, Oleg A.; Boyd, Eric S.; Posewitz, Matthew C.; Zorin, Nikolay A.; Peters, John W. (Frontiers in Bioengineering and Biotechnology, 2015)
Enolase catalyzes the conversion of 2-phosphoglycerate to phosphoenolpyruvate during both glycolysis and gluconeogenesis and is required by all three domains of life. Here, we report the purification and biochemical and structural characterization of enolase from Chloroflexus aurantiacus, a thermophilic andanoxygenic phototroph affiliated with the green non-sulfur bacteria. The protein was purified as a homodimer with a subunit molecular weight of 46 kDa. The temperature optimum for enolase catalysis was 80°C, close to the measured thermal stability of the protein which was determined to be 75°C, while the pH optimum for enzyme activity was 6.5. The specific activities of purified enolase determined at 25°C and 80°C were 147 and 300 units/mg of protein, respectively. Km values for the 2-phosphoglycerate/phosphoenolpyruvate reaction determined at 25°C and 80°C were 0.16 mM and 0.03 mM, respectively. The Km values for Mg2+ binding at these temperatures were 2.5 mM and 1.9 mM, respectively. When compared to enolase from mesophiles, the biochemical and structural properties of enolase from C. aurantiacus are consistent with this being thermally adapted. This data is consistent with the results of our phylogenetic analysis of enolase, which reveal that enolase has a thermophilic origin.